2021
DOI: 10.1002/ldr.4087
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial taxa and fungal diversity are the key factors determining soil multifunctionality in different cropping systems

Abstract: Soil microbes in the topsoil have long been the centre of cropping systems, yet the influence of subsoil microbes on soil functions remains elusive. Sustainable crop management will require an in-depth understanding of interactions of cropping patterns, soil microbials and multifunctionality. This study aimed to explore the relationships between soil microbials and multifunctionality in both topsoil and subsoil of different cropping systems. We did paired samplings from four cash crops and adjacent wheat/ maiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Plant diversity and soil factors were found to be vital in predicting microbial community changes in soil (Liu et al, 2020;Zeng et al, 2017;Zhang et al, 2016) Zhang et al, 2021;Zheng et al, 2019). Similarly, our research clearly revealed the importance of plant diversity and pH in promoting soil microbial community.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Plant diversity and soil factors were found to be vital in predicting microbial community changes in soil (Liu et al, 2020;Zeng et al, 2017;Zhang et al, 2016) Zhang et al, 2021;Zheng et al, 2019). Similarly, our research clearly revealed the importance of plant diversity and pH in promoting soil microbial community.…”
Section: Discussionsupporting
confidence: 64%
“…Plant diversity and soil factors were found to be vital in predicting microbial community changes in soil (Liu et al, 2020; Zeng et al, 2017; Zhang et al, 2016) and multifunctionality (Lucas‐Borja & Delgado‐Baquerizo, 2019; Xue et al, 2020). More and more researches have recently identified soil bacteria as a critical factor influencing soil multifunctionality (Delgado‐Baquerizo et al, 2020; Zhang et al, 2021; Zheng et al, 2019). Similarly, our research clearly revealed the importance of plant diversity and pH in promoting soil microbial community.…”
Section: Discussionmentioning
confidence: 99%
“…The heightened importance of fungi over bacteria in forest soils, potentially due to the presence of abundant recalcitrant substrates like lignin polymers, which are associated with the strong degradative capacity of fungi, may provide an explanation for this disparity. Interestingly, a prior study discovered that in agroecosystems, soil multifunctionality was jointly regulated by both bacterial and fungal communities [60]. This observation underscores the significance of adequate organic material inputs, which encompass a diverse array of both labile and recalcitrant carbon substrates, highlighting the interconnected role of both bacterial and fungal communities in shaping soil multifunctionality.…”
Section: Fungal Community Regulate Soil Multifunctionality Rather Tha...mentioning
confidence: 82%
“…Cereal–forage rotation presented little effects on rhizosphere microbial alpha diversity, but greater effects on beta diversity (Figures 1 and 2), which are consistent with previous results that despite lower microbial α‐diversity variations, obvious changes in β‐diversity could still be observed (Griffiths et al, 2011; Lozupone et al, 2007). The changes of microbial community composition could significantly promote plant production and soil multifunctionality (Li et al, 2021; Yan et al, 2022; Zhang et al, 2021). Some microbial groups shaped by rotation regime show strong effects on soil functions such as organic matter decomposition and nutrient cycling (D'Acunto et al, 2018; Fernandez et al, 2016; Nazaries et al, 2021).…”
Section: Discussionmentioning
confidence: 99%